Assessing health risks to local population from contamination sources in and around Sulaimani province; a qualitative study - Othman, Nasih; Kane, Thomas; Hawrami, Karzan Mohammed; Alkaradaghi, Karwan; Salih, Faisal Abdullah; Abdullah, Tareq hama amin; Hamafaraj, Kawa Khwa Rahim; Ali, Tara (Sulaimani Journal for Pure and Applied Sciences, 2018)
There are many physical, chemical and biological agents either naturally present or produced by human activity that can be hazardous for human health. Environmental pollution in and around Sulaymaniyah city is caused by several factors including untreated wastewater, contaminated agricultural fields, untreated solid waste, industrial waste and contamination of Tanjaro River and Darbandikhan Lake from these sources of pollution. Populations, especially those living closer to the above-mentioned pollution sources are at risk of both short and long-term effects of biological, physical and chemical contaminants, especially south of the city and around Tanjaro River and Darbandikhan Lake. Neglecting these problems means that buildup of contaminants in the environment and endangering population health will continue. Monitoring and responding to environmental health hazards requires collaborative efforts of relevant departments, professional institutions, NGOs, community-based organizations and affected populations. To reduce risk of water-borne diseases is strengthening water management in relation to maintaining quality while the ultimate solution to wastewater pollution is establishment of sewerage treatment plants. Solid waste is a major problem and the ultimate solution is recycling and the establishment of a controlled landfill in an area. Immediate measures need to be taken to prevent further pollution of the Tanjaro River, by isolating the polluting sources. Industrial activities need to be regulated and monitored in terms of environmental and occupational safety operations and standards. Using Sulaymaniyah wastewater for farming must be prohibited by law and enforced. Protection of Darbandikhan Lake from major sources of pollution should be made a higher priority and measures should be taken as soon as possible to isolate and minimize major pollutants. There is also a need for extensive research and the establishment of sustained research systems on population health and environmental pollutants, especially in relation to the food chain, and the Tanjaro River, Darbandikhan Lake and air pollution. If urgent consideration is not given to the above areas and problems, the situation may get considerably worse in the coming years.
Keywords: Health risk assessment; drinking water; liquid waste diposal; solid waste diposal and industrial pollution